The electroneutrality approximation in electrochemistry - Dickinson, E; Limon-Petersen, J; Compton, R (2011)
The electroneutrality approximation assumes that charge separation is impossible in electrolytic solutions. It has a long and successful history dating back to 1889 and may be justified because of the small absolute values for the permittivities of typical solvents. Dimensional analysis shows that the approximation becomes invalid only at nanosecond and nanometre scales. Recent work, however, has taken advantage of the capabilities of modern numerical simulation in order to relax this approximation, with concomitant advantages such as avoiding paradoxes and permitting a clear and consistent 'physical picture' to describe charge dynamics in solution. These new theoretical techniques have been applied to liquid junction potentials and weakly supported voltammetry, with strong experimental corroboration for the latter. So long as dynamic processes are being studied, for which analytical solutions are unavailable in any case, numerical simulation is shown to render electroneutrality unnecessary as an a priori assumption. © 2011 Springer-Verlag.